Особенности бредовой фабулы депрессивно-параноидного синдрома у контингента пациентов пожилого и старческого возраста, страдающих кардиоваскулярной патологией - Liskonog, A. G. (Journal of Education, Health and Sport, 2015)
Liskonog A. G. Особенности бредовой фабулы депрессивно-параноидного синдрома у контингента пациентов пожилого и старческого возраста, страдающих кардиоваскулярной патологией = Features of dellusive plot of depressive-paranoid syndrome in cohort of patients of elderly and senile age suffering from cardiovascular pathology. Journal of Education, Health and Sport. 2015;5(9):209-216. ISSN 2391-8306. DOI10.5281/zenodo.30530 http://dx.doi.org/10.5281/zenodo.30530 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A209-216 https://pbn.nauka.gov.pl/works/619866 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 29.08.2015. ОСОБЕННОСТИ БРЕДОВОЙ ФАБУЛЫ ДЕПРЕССИВНО-ПАРАНОИДНОГО СИНДРОМА У КОНТИНГЕНТА ПАЦИЕНТОВ ПОЖИЛОГО И СТАРЧЕСКОГО ВОЗРАСТА, СТРАДАЮЩИХ КАРДИОВАСКУЛЯРНОЙ ПАТОЛОГИЕЙ FEATURES OF DELLUSIVE PLOT OF DEPRESSIVE-PARANOID SYNDROME IN COHORT OF PATIENTS OF ELDERLY AND SENILE AGE SUFFERING FROM CARDIOVASCULAR PATHOLOGY А. Г. Лисконог A. G. Liskonog Запорожский Государственный медицинский университет Zaporozhzhia State Medical University Abstract In order to analyze clinical features of delusive plot of depressive-paranoid syndrome among the cohort of patients of elderly and senile age, suffering from cardiovascular pathology, 100 patients of elderly and senile age, of psychosomatic department № 24 TMO "Psychiatry", Kiev, with the dominant depressive-paranoid syndrome in the structure of psychopathological disorders, was investigated. The study developed a classification of types of clinical arrangement of depressive-paranoid syndrome, among the studied cohort of patients, 9 types of clinical arrangement were allocated: anxious -persecutory, anxious-hypochondrical, anxious-self-blaming, apathetically-persecutory, apathetically-hypochondrical, apathetically-self-blaming, melancholically-persecutory, melancholically- hypochondrical, melancholy-self-blaming. Key words: depressive-paranoid syndrome; arrangement; anxiety; melancholy; psychogerontology.